The philosophy argument in proving validity of Al-Qur’an: Thematic analysis on the thought of Said Al-Nursi / Amad Kadhim M. Salih - Amad Kadhim, M. Salih (2015)
This study resulted in the ideological and philosophical methodology submissions to disclose the truth of the Quran and prove the superiority of the philosophical, theoretical material and his school of thoughts. This study was conducted on selected topics from the book "Rasaili al-Nur" from the aspect of strengthening the foundations of faith and the attack on the Muslim mindset. This study began with the introduction of the history of al-Nursi Bediuzzaman life and thoughts as well as his scientific publications. In addition, this chapter also reveal the new approach in a more philosophical arguments to support and glorify the truth of the Quran as well as refuting conflicting with it. The researcher also displays the strengths and weaknesses of athest thought (ilhadiyah) on issues related to Rububiyyah and Uluhiyyah. Surely the obvious fact clearly proves the existence of God and Rububiyyah and Uluhiyyah by explanations of the Quran. Likewise, evidence of submission of the aspects of philosophy, theology, logic and scientific. In the second chapter the researcher presents strong evidence in language and linguistics aspects, the arrangement of wording, style, language, science and the knowledge contained in the Quran and argue that there is confusion in the language of the Quran and the scientific evidence. The researcher also discussed issues related to the justice of God in all creation and creative as well as the evidence and arguments about the existence of God based on the evidence in the third chapter. Also discussed in this chapter is the issue of creation without a middleman, a refutation of Darwin's theory of evolution and the theory of natural selection, which includes the study of fairness in education and behavioral, social, legal and economic conditions in the Quran, and reject errors or suspicion raised about the justice of God. In the fourth chapter the researcher has explained some of the terms (civilization, universality and globalization). Indeed, researchers have been able to prove the accuracy of the two concepts of civilization and universality in the Quran and civilization and globalization relate to the western world. After the process of academic evaluation of faiths is the researcher has reached the stage that Islamic civilization has overtaken western civilization. Chapter 5 describes the concept of al-Hikmah and al-philosophy based on the Quran, the integration of the concept of philosophy as well as the height of the concept of humanity through knowledge of the Quran and its proximity to the philosophy of positivism.